Novel Metabolic Attributes of the Genus Cyanothece, Comprising a Group of Unicellular Nitrogen-Fixing Cyanobacteria - Anindita Bandyopadhyay (American Society for Microbiology, 2011)
ABSTRACT The genus Cyanothece comprises unicellular cyanobacteria that are morphologically diverse and ecologically versatile. Studies over the last decade have established members of this genus to be important components of the marine ecosystem, contributing significantly to the nitrogen and carbon cycle. System-level studies of Cyanothece sp. ATCC 51142, a prototypic member of this group, revealed many interesting metabolic attributes. To identify the metabolic traits that define this class of cyanobacteria, five additional Cyanothece strains were sequenced to completion. The presence of a large, contiguous nitrogenase gene cluster and the ability to carry out aerobic nitrogen fixation distinguish Cyanothece as a genus of unicellular, aerobic nitrogen-fixing cyanobacteria. Cyanothece cells can create an anoxic intracellular environment at night, allowing oxygen-sensitive processes to take place in these oxygenic organisms. Large carbohydrate reserves accumulate in the cells during the day, ensuring sufficient energy for the processes that require the anoxic phase of the cells. Our study indicates that this genus maintains a plastic genome, incorporating new metabolic capabilities while simultaneously retaining archaic metabolic traits, a unique combination which provides the flexibility to adapt to various ecological and environmental conditions. Rearrangement of the nitrogenase cluster in Cyanothece sp. strain 7425 and the concomitant loss of its aerobic nitrogen-fixing ability suggest that a similar mechanism might have been at play in cyanobacterial strains that eventually lost their nitrogen-fixing ability. IMPORTANCE The unicellular cyanobacterial genus Cyanothece has significant roles in the nitrogen cycle in aquatic and terrestrial environments. Cyanothece sp. ATCC 51142 was extensively studied over the last decade and has emerged as an important model photosynthetic microbe for bioenergy production. To expand our understanding of the distinctive metabolic capabilities of this cyanobacterial group, we analyzed the genome sequences of five additional Cyanothece strains from different geographical habitats, exhibiting diverse morphological and physiological attributes. These strains exhibit high rates of N2 fixation and H2 production under aerobic conditions. They can generate copious amounts of carbohydrates that are stored in large starch-like granules and facilitate energy-intensive processes during the dark, anoxic phase of the cells. The genomes of some Cyanothece strains are quite unique in that there are linear elements in addition to a large circular chromosome. Our study provides novel insights into the metabolism of this class of unicellular nitrogen-fixing cyanobacteria.